2010
DOI: 10.1016/j.jacc.2009.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Antimicrobial Agent on Atherosclerotic Plaques

Abstract: Molecular imaging of MMP activity in atherosclerotic plaque allows for the study of the efficacy of therapeutic interventions. MC administration resulted in substantial reduction in plaque MMP activity and histologically verified plaque stabilization. MC was found to be equally effective as FS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…Unlike their effects in humans, the effects of statins on serum lipid levels and plaque burden and composition in the mouse are inconsistent and appear to depend on experimental conditions (14, 16, 17). This may explain the differences between our findings and those of previous investigations in rabbits (9, 18). Fibrates, such as fenofibrate, regulate blood lipid levels through their agonistic effect on peroxisome proliferator receptor (PPAR) α signaling (19).…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike their effects in humans, the effects of statins on serum lipid levels and plaque burden and composition in the mouse are inconsistent and appear to depend on experimental conditions (14, 16, 17). This may explain the differences between our findings and those of previous investigations in rabbits (9, 18). Fibrates, such as fenofibrate, regulate blood lipid levels through their agonistic effect on peroxisome proliferator receptor (PPAR) α signaling (19).…”
Section: Discussioncontrasting
confidence: 99%
“…SPECT studies based on these panMMP-specific agents detect MMP active forms in ventricular and vascular remodeling and can be used to predict aneurysm rupture in the mouse212223. MMP signal often correlates with tissue inflammation and is reduced in response to therapeutic interventions242526. Given the diverse, and at time opposite roles that MMPs play in cardiovascular pathology, imaging a specific member of MMP family could provide additional information regarding specific cardiovascular pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated the feasibility of imaging MMPs (and other relevant targets) using various imaging modalities in animal models of atherosclerosis (5,8,15,22,23). The high sensitivity of nuclear imaging (PET, SPECT) and its applicability to human studies make it an especially promising approach for studies of vessel wall biology in vivo.…”
Section: Discussionmentioning
confidence: 99%